2022
DOI: 10.3390/jcm11113116
|View full text |Cite
|
Sign up to set email alerts
|

When to Achieve Complete Revascularization in Infarct-Related Cardiogenic Shock

Abstract: Acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) is a life-threatening condition frequently encountered in patients with multivessel coronary artery disease (CAD). Despite prompt revascularization, in particular, percutaneous coronary intervention (PCI), and therapeutic and technological advances, the mortality rate for patients with CS related to AMI remains unacceptably high. Differently form a hemodynamically stable setting, a culprit lesion-only (CLO) revascularization strategy is cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…15,16 The evidence from a meta-analysis conducted in this aspect has shown that the risk of adverse outcomes can be reduced by achieving complete revascularization in STEMI patientsparticularly in those with MVD. 17 In our study, patients had a mean age of 50.10±10.74 years with a mean age of 49.56±10.24 years in cases and 50.64±11.25 years in controls. The majority of the patients were males (68%), 36%in the case group and 32% in the control group with an insignificant p-value of 0.225.…”
Section: Discussionmentioning
confidence: 60%
“…15,16 The evidence from a meta-analysis conducted in this aspect has shown that the risk of adverse outcomes can be reduced by achieving complete revascularization in STEMI patientsparticularly in those with MVD. 17 In our study, patients had a mean age of 50.10±10.74 years with a mean age of 49.56±10.24 years in cases and 50.64±11.25 years in controls. The majority of the patients were males (68%), 36%in the case group and 32% in the control group with an insignificant p-value of 0.225.…”
Section: Discussionmentioning
confidence: 60%
“…The CULPRIT-SHOCK (Culprit Lesion Only PCI Versus Multi-vessel PCI in Cardiogenic Shock) trial demonstrated that culprit-only percutaneous coronary intervention (PCI) was superior to immediate multivessel PCI in terms of short-term mortality [29]; however, when and how to employ non-culprit lesion revascularization strategy in refractory CS requiring MCS remains controversial [30,31]. Future randomized trials are warranted to determine the definitive role of a tailored complete revascularization (whether anatomical or functional) in an AMI with CS scenario and the timing of complete revascularization during MCS-supported index PCI or in a staged PCI after the acute phase [32,33]. Although the role of emergency coronary artery bypass grafting is currently underrated, surgical revascularization still represents an important treatment option in selective scenarios, and the research on surgical revascularization of refractory CS requiring MCS is lacking [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the policy of COVID-19 virus nucleic acid testing normalization has shocked the conventional emergency, surgical, and other medical practices because of prolonged preoperative waiting (6). Patients under life-threatening emergent circumstances, such as acute myocardial infarction and strangulated intestinal obstruction, cannot bear such a long wait, while patients with other emergent situations, including ruptured intracranial aneurysm, were reported to tolerate the wait and exhibit similar outcomes as patients without the wait for result of virus nuclei acid detection (20)(21)(22)(23). However, there remains little literature discussing the influence of the policy of COVID-19 virus nucleic acid testing normalization on emergency digit replantation.…”
Section: Discussionmentioning
confidence: 99%